2022
DOI: 10.1038/s42003-022-03743-9
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal sex patterns p21-induced cellular senescence in mouse and human glioblastoma

Abstract: Males exhibit higher incidence and worse prognosis for the majority of cancers, including glioblastoma (GBM). Disparate survival may be related to sex-biased responses to treatment, including radiation. Using a mouse model of GBM, we show that female cells are more sensitive to radiation, and that senescence represents a major component of the radiation therapeutic response in both sexes. Correlation analyses revealed that the CDK inhibitor p21 and irradiation induced senescence were differentially regulated b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 50 publications
2
8
0
Order By: Relevance
“…An accompanying analysis of survival data from 3.7 million cases in the SEER database, representing approximately 28% of the cancer population, confirmed that mortality rates are higher for males compared to females [2]. These clinically important sex differences are concordant with described sex differences in cell biology including, response to genotoxic stress [3,4], DNA repair [5,6], mutational burden [7,8], metabolism [9,10], and cell cycle regulation [11][12][13], as well as in systems biology including: immunity [14], metabolism [15,16], tissue repair [17,18], and longevity [19,20]. This suggests that therapies for all cancer patients may be advanced by a realistic translation of sex differences into clinical practice.…”
Section: Introductionmentioning
confidence: 60%
“…An accompanying analysis of survival data from 3.7 million cases in the SEER database, representing approximately 28% of the cancer population, confirmed that mortality rates are higher for males compared to females [2]. These clinically important sex differences are concordant with described sex differences in cell biology including, response to genotoxic stress [3,4], DNA repair [5,6], mutational burden [7,8], metabolism [9,10], and cell cycle regulation [11][12][13], as well as in systems biology including: immunity [14], metabolism [15,16], tissue repair [17,18], and longevity [19,20]. This suggests that therapies for all cancer patients may be advanced by a realistic translation of sex differences into clinical practice.…”
Section: Introductionmentioning
confidence: 60%
“…The major contributing factor to cell senescence is DNA damage (Durik et al, 2012; Yousefzadeh et al, 2021). From the existing literature, female sex is associated with reduced capacity for DNA repair in different organs and cell types (Broestl et al, 2022; Kfoury et al, 2018; Malorni et al, 2008; Rallā€Scharpf et al, 2021; Sun et al, 2014; Trzeciak et al, 2008), with one exception to this assumption found by Yousefzadeh et al (2020). Walker et al found that age (>55 y/o) has a greater effect on activating DNA damage response and senescence in aged women compared with aged men (Walker et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Commonly, male fetuses have a bigger morphometric body compared with female fetuses [4]. Cells in male fetuses have higher numbers than in females [5]. The different cells number affected by the size of a muscle, a male fetus has a bigger muscle size.…”
Section: Introductionmentioning
confidence: 99%